Immunogenicity and safety of a combined DTPa-IPV/Hib vaccine administered as a three-dose primary vaccination course in healthy Korean infants: phase III, randomized study. Issue 2 (1st February 2019) - Kim, Ki Hwan; Kim, Chun Soo; Kim, Hwang Min; Kim, Jong-Duck; Ma, Sang Hyuk; Kim, Dong Ho; Hwang, Pyoung-Han; Han, Ji-Whan; Lee, Taek-Jin; Kim, Joon Hyung; Karkada, Naveen; Mesaros, Narcisa; et al.
ABSTRACT: We assessed the immunogenicity and safety of a three-dose primary vaccination schedule with the combined diphtheria-tetanus-acellular pertussis-inactivated poliovirus/Haemophilus influenzae type b vaccine (DTPa-IPV/Hib) in Korean infants. In this phase III open-label, multicenter study (NCT01309646), healthy infants aged 42–69 days (randomized 1:1) received three doses of either pentavalent DTPa-IPV/Hib (DTPa-IPV/Hib group) or DTPa-IPV and Hib vaccines administered separately (DTPa-IPV+Hib group) at 2, 4, 6 months of age. The primary objective was to demonstrate non-inferiority of DTPa-IPV/Hib compared to DTPa-IPV+Hib vaccines in terms of immune responses to all vaccine antigens, 1 month post-dose 3. Solicited symptoms (local and general) were recorded during 4 days, and unsolicited adverse events (AEs) during 31 days, after each vaccination. Serious AEs (SAEs) were recorded throughout the study duration. The immunogenicity of the pentavalent DTPa-IPV/Hib vaccine was non-inferior compared to concomitant administration of DTPa-IPV+Hib vaccines. One month post-dose 3, nearly all infants had antibody levels above the seroprotective thresholds for anti-diphtheria toxoid, anti-tetanus toxoid, anti-polyribosyl-ribitol phosphate, and anti-poliovirus type 1, 2 and 3, and had antibody levels above the seropositive thresholds for anti-pertussis toxoid (PT), anti-filamentous hemagglutinin (FHA) and anti-pertactin (PRN) antibodies. A vaccine response for PT, FHA and PRN was observed in at least 96.7% of study participants. Anti-PRP geometric mean concentrations appeared lower for the DTPa-IPV/Hib group (8.456 µg/mL) than for the DTPa-IPV+Hib group (18.700 µg/mL). In both groups, the most common solicited symptoms were injection site redness and irritability. Fifty-seven SAEs were reported throughout the study; none were considered to be vaccination related.